Mediation Effect of Research Skills Proficiency on the Core Self-Evaluations – Research Engagement Relationship among Master of Education Students in Uganda - Atibuni, Dennis Zami; Olema, David Kani; Ssenyonga, Joseph; Karl, Steffens; Kibanja, Grace Milly (Journal of Education and Practice, 2017)
This study investigated the mediation effect of research skills proficiency on the relationship between core self-evaluations and research engagement among Master of Education students in Uganda. Questionnaire surveys including closed ended questions were administered to two cohorts of the students, 2011/2012 and 2012/2013, (N = 102). Results indicated total mediation effect of research skills proficiency on the relationship between core self-evaluations and research engagement. Implications for educational practice include careful selection and training of adult learners at master’s level on the basis of their core self-evaluations levels; individuals with positive core self-evaluations should be accorded priority entry into the programme. Implications for future research include carrying out intervention studies on how to effectively impart 21st century skills in the adult learners.
Keywords: Core self-evaluations; Research skills proficiency; Research engagement; Mediation effect; Master of Education; Uganda; 21st Century skills